A KARAKTERISTIK PUTU AYU DENGAN SUBSTITUSI UBI JALAR UNGU: Substitusi Putu Ayu Ubi Jalar Ungu - Wulandari, Yesi Dwi; Holinesti, Rahmi; Faridah, Anni; Siregar, Juliana (Department of Food Technology, Universitas Pasundan, Bandung, 2025)
This study aims to determine the effect of purple sweet potato (Ipomoea batatas L.) substitution on the organoleptic quality of putu ayu, evaluated based on shape, color, aroma, texture, and taste. The research employed a Completely Randomized Design (CRD) with four levels of purple sweet potato substitution (0%, 10%, 20%, and 30%) and three replications. Organoleptic tests were conducted with 30 untrained panelists using a structured rating scale. The results showed that treatment X0 (0%) yielded the best scores for shape and taste, while treatment X3 (30%) provided the best results for color, aroma, and texture softness. Statistical analysis indicated that purple sweet potato substitution had a significant effect on color, aroma, and taste, but no significant effect on shape and volume expansion. In conclusion, up to 30% purple sweet potato substitution can improve the appearance and aroma of putu ayu, although flavor balance should be considered.